تأثير بعض العناصر المناخية في إنتاجية اللوز Amygdalus communis في حلب وحماة وحمص - جلب أدهم (Latakia University Journal -Biological Sciences Series, 2018)
أظهرت النتائج تراجع إنتاجية شجرة اللوز(كغ) خلال فترة الدراسة في حلب وحماة وحمص وبلغت على التوالي (5.448-، 3.38-، 1.134-) كغ / شجرة مع معامل تغير بلغ (34.11، 49.46، 66.66 )، مما يشير إلى أن أفضل استقرار للإنتاج هو في حلب تليه حماة ثم حمص. تم حساب معدل التراكمات الحرارية الفعالة ( 3221.19 3347, 2993.51, ) والنشطة(4505, 44764209, ) اللازمة للفترة من نهاية الإزهار وحتى نضج ثمار اللوز في المحافظات الثلاث على التوالي. كما تم تحديد انحراف الإنتاجية الحقيقية عن الإنتاجية المحسوبة كنسبة مئوية خلال سنوات الدراسة في مناطق الدراسة. من خلال دراسة اتجاه تغير الإنتاجية جرى ترتيب السنوات الملائمة والسنوات غير الملائمة لإنتاجية اللوز في المناطق الثلاث استناداً إلى قيم حصة الظروف المناخية والتي تم تقسيمها إلى خمس مستويات من الملاءمة. تشير نتائج معادلات الارتباط المتعدد إلى وجود ارتباط قوي لهذه المعادلات تراوحت قيمته بين (0.80 وحتى 0.92) والتي تربط بين إنتاجية اللوز وتأثير أهم ستة عوامل مناخية مؤثرة ( سلباً أو إيجاباً) خلال أطوار النمو المختلفة في محافظات حلب وحماة وحمص. Results showed that the yield average rate of Amygdalus communis decreased during the study period in Aleppo, Hama and Homs. It reached 5.448 - ) , 3.38- ,-1.134) kg/tree and CV% in (34.11 , 49.46،, ( 66.66respectively. This indicates that stability in Aleppo is better than Hama and latter Homs. Thermal effective (3221.19, 3347, 2993.51) and active (4505, 4476, 4209) accumulations average are calculated from the period of flowering end to maturity in Aleppo, Hama and Homs respectively. Moreover the real productive ratio as compared with the calculated one was defined in percentage terms during the years of study. Analysis of the change in productivity tendency led to classification of years as convenient or inconvenient based on the share of climatological factors in the three areas in five levels of convenience. Multi-correlation coefficient values (+0.80 and +0.92) indicated strong positive influence on Amygdalus communis yield, and correlated between Amygdalus communis yield and the six most important climatological elements affecting almond trees during the pheonological stages in Aleppo, Hama and Homs.